(untitled) (Malaysian Journal of Civil Engineering, 2018)
Engaging critical thinking and mathematical thinking in solving engineering problems is complying ABET engineering criteria. Thus, the understanding of interaction between these two thinking is critical for the current engineering education. However, the interaction is not thoroughly being studied in the real-world engineering practice. This paper describes the selection process of the pertinent elements of critical thinking and mathematical thinking and the interrelation among the elements in the real-world civil engineering practice, using modified grounded theory analysis. Data consisted of semi-structured interviews with eight practicing civil engineers from two consultancy firms. A total of fifty three pertinent elements emerged during open coding process. Axial coding process developed the interrelation among the pertinent elements. The findings showed that during design process, the elements were interwoven, concurrently used, indispensable and inexorably linked. Thus, the results provide main source of information to explain the interaction among pertinent elements in selective coding process.